Skrining Anemia Melalui Pemeriksaan HB, TIBC dan Serum Iron Pada Remaja Putri di SMK Baitul Hikmah Tempurejo - Handayani, Ririn; Anggraeni, Ernawati; Handayani, Yuni; Kumala D, Yashinta (FKM UIN Sumatera Utara Medan, 2023)
Anemia is a public health problem in Indonesia that can be experienced by all age groups, from toddlers to the elderly. One of them is young women, where these young women are prone to anemia due to a lot of blood loss during menstruation, young women who are entering puberty experience rapid growth so that the need for iron also increases and there is an incorrect diet pattern in rhymes. Adolescent girls who suffer from anemia are also at risk of developing anemia during pregnancy. This will have a negative impact on the growth and development of the fetus in the womb and has the potential to cause complications during pregnancy and childbirth. The purpose of this activity is to screen for iron deficiency anemia in young women as a preventive measure for anemia in adolescents which can cause long-term adverse effects on adolescents.Screening for iron deficiency anemia in this activity was carried out through laboratory examination of panel iron levels, especially TIBC and Serum Iron examinations in young girls. The target for this activity is young women at Baitul Hikmah Tempurejo Vocational School. Screening begins with anamnesis and physical examination. If there are indications that lead to anemia, an iron panel examination (TIBC and serum iron) will be performed. The results obtained will be analyzed and consulted with the local regional health officer to get the right treatment